Gastrointestinal Ultrasound Can Predict Endoscopic Activity in Crohn’s Disease - Sævik, Fredrik; Gilja, Odd Helge; Nylund, Kim (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Purpose To explore the ability of gastrointestinal ultrasound (GIUS) to separate patients in endoscopic remission from patients with active disease in a heterogeneous hospital cohort with Crohn’s disease (CD).Materials and Methods 145 CD patients scheduled for ileocolonoscopy were prospectively included. The endoscopic disease activity was quantified using the Simple Endoscopic Score for Crohn’s disease (SES-CD), and mucosal healing was strictly defined as SES-CD = 0. Ultrasound remission was defined as wall thickness < 3 mm (< 4 mm in the rectum). Additionally, SES-CD was compared to color Doppler, Harvey Bradshaw’s index (HBI), C-reactive protein (CRP) and calprotectin. 23 patients were examined by two investigators for interobserver assessment.Results 102 had active disease and 43 patients were in remission. GIUS yielded a sensitivity of 92.2 % and a specificity of 86 % for wall thickness and a sensitivity of 66.7 % and a specificity of 97.7 % for color Doppler. The sensitivity and specificity were 34.3 % and 88.4 %, respectively, for HBI, 35.7 % and 82.9 %, respectively, for CRP and 55.9 % and 82.1 %, respectively, for calprotectin. The interobserver analysis revealed excellent agreement for wall thickness (k = 0.90) and color Doppler (k = 0.91) measurements.Conclusion GIUS has a high sensitivity for detecting endoscopic activity. Accordingly, bowel ultrasound has the potential to reduce the number of routine ileocolonoscopies in patients with CD.
Keywords: Crohn’s disease; gastrointestinal ultrasound; monitoring; mucosal healing